Detecting the vulnerable plaque in patients. (26th August 2015) - Gonçalves, I.; den Ruijter, H.; Nahrendorf, M.; Pasterkamp, G.
Abstract: Atherosclerosis is a systemic condition that eventually evolves into vulnerable plaques and cardiovascular events. Pathology studies reveal that rupture‐prone atherosclerotic plaques have a distinct morphology, namely a thin, inflamed fibrous cap covering a large lipidic and necrotic core. With the fast development of imaging techniques in the last decades, detecting vulnerable plaques thereby identifying individuals at high risk for cardiovascular events has become of major interest. Yet, in current clinical practice, there is no routine use of any vascular imaging modality to assess plaque characteristics as each unique technique has its pros and cons. This review describes the techniques that may evolve into screening tool for the detection of the vulnerable plaque. Finally, it seems that plaque morphology has been changing in the last decades leading to a higher prevalence of 'stable' atherosclerotic plaques, possibly due to the implementation of primary prevention strategies or other approaches. Therefore, the nomenclature of vulnerable plaque lesions should be very carefully defined in all studies.